2015
DOI: 10.1364/ao.54.003018
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping-free phase retrieval with applications to interferometry, 3D-shape profiling, and deflectometry

Abstract: Phase unwrapping is probably the most challenging step in the phase retrieval process in phase-shifting and spatial-carrier interferometry. Likewise, phase unwrapping is required in 3D-shape profiling and deflectometry. In this paper, we present a novel phase retrieval method that completely sidesteps the phase unwrapping process, significantly eliminating the guessing in phase reconstruction and thus decreasing the time data processing. The proposed wrapping-free method is based on the direct integration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The wrapping-free phase retrieval method proposed by Perciante et. al has been thoroughly described and discussed [34], this section only introduces its main idea briefly. Suppose Perciante's method is applied to four-step phase-shifting fringe.…”
Section: Perciante's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wrapping-free phase retrieval method proposed by Perciante et. al has been thoroughly described and discussed [34], this section only introduces its main idea briefly. Suppose Perciante's method is applied to four-step phase-shifting fringe.…”
Section: Perciante's Methodsmentioning
confidence: 99%
“…Recently, Perciante et. al [34] presented a wrapping-free phase retrieval method. It determines the phase of the test object following two steps: first, it derives two partial derivatives of the desired phase from the fringe patterns, and then it reconstructs the phase by the line integral of the two partial derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Least-Squares algorithm shows the inherent defects that flatten the peak value and fill the valley value during phase unwrapping, which will significantly decrease unwrapping performance. Perciante et al [14] proposed the wrapping-free unwrapping algorithm, which yields derivatives of the required horizontal and vertical phase from the corresponding fringe image and reconstructs the phase by calculating the two partial derivatives. Similar to the referenced algorithms [15][16], it converts the integral of the mentioned space derivatives as a solution to the Poisson equation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this method can obtain good unwrapping results at discontinuities. Based on the wrapping-free phase retrieval method described in [17], Zhou et al [18] proposed a binary mask of a reverse DVCM as the weight mask. Since the second derivative of the four-step phaseshifting fringe pattern needs to be calculated, these methods are only suitable for particular measurement objects with singularities.…”
Section: Introductionmentioning
confidence: 99%